THE EFFECTIVENESS OF THE (WITTROCK) MODEL IN PREVENTION AWARENESS AMONG THIRD GRADE MIDDLE SCHOOL STUDENTS AND THEIR COGNITIVE CURIOSITY - Ahmed Abbas Karim (European Journal of Humanities and Educational Advancements, 2024)
The current research aims to identify the effectiveness of the Wittrock model in the Prevention Awareness of third-grade middle school students and their cognitive curiosity, to achieve this, an experiment was conducted that took about two months, as the researcher deliberately selected the Hammurabi medium for boys as a sample for research, and the 195 middle school thirdgrade students were divided into 4 people, of whom two groups were randomly selected by 38 students for the control group and 38 students for the experimental group, after which the two groups were rewarded in variables IQ - age - cognitive curiosity - Prevention Awareness and the researcher adopted the experimental design with partial control of two equal groups, and the extraneous variables were adjusted, and the experiment was applied in the first semester of the academic year 2023-2024. After the experiment, the results were analyzed statistically using the T-test for two independent eyes and concluded that there were statistically significant differences in favor of the experimental group in the two scales of Prevention Awareness and cognitive curiosity.